Globalization and world society - Spybey, Tony (Polity Press, 1996)
Globalization and World Society traces the early development of global culture through the rise of Western civilization and the impact of that civilization upon the non-industrialized world. Its main concern is to examine the various institutions which emerged from this process - citizenship and the nation-state system, producer/consumers and global economy, 'viewers' and the global communication system, soldiers and the world order, protesters and the global movements. The emphasis throughout is on reflexive connections between individuals and global institutions. The author considers different theoretical approaches to the analysis of globalization but also discusses a rich variety of more empirical issues and materials. This book will appeal to second- and third-year undergraduates following courses which deal with processes of globalization.
Keywords: Concurrence internationale; Coopération internationale; Economische betrekkingen; Histoire économique - 1945-; Internationale orde; Internationale samenwerking; Internationalisatie; Mondialisation; Globalisierung; Weltwirtschaft; Wirtschaft. Geschichte; Competition, International; Economic history -- 1945-; International cooperation; International economic relations; Weltgesellschaft; Massengesellschaft; Westliche Welt